Individual, collective and contextual dimensions of sustainable lifestyle change in daily life contexts: an integrated perspective - De Gregorio, Eugenio; Carrus, Giuseppe; Klöckner, Christian Andreas; Löfström, Erica; Similä, Lassi; Brenner-Fliesser, Michael (Frontiers in Psychology, 2025)
This paper aims to develop a conceptual and theoretical perspective on sustainable lifestyle change according to a multidisciplinary approach. In particular, we discuss the interplay between three orders of factors that, according to the literature and to our conceptual model, are relevant in shaping sustainable lifestyles and lifestyle change in people daily life contexts, such as their living neighbourhoods. The three orders of factors are the following: (1) Individual level factors (as typically present and discussed in the environmental psychology literature; e.g., attitudes, values, beliefs, intentions, emotions, connection to nature, etc.); (2) Collective level factors (as typically present and discussed in the social psychology and sociology literature; e.g., social capital, social norms, social and place identity, sense of community, place attachment, energy memories & energy cultures); (3) Contextual factors (as typically present and discussed in the environmental science and economic literature; e.g., regulations, technology, infrastructures, economic resources, etc.). For each of these three levels, we will present and discuss some classical and recent literature findings, and we will provide a summary of the current state of the art knowledge about sustainable lifestyle adoption in neighbourhoods’ contexts.